-15x
2006-12-15 08:06:07
·
answer #1
·
answered by raj 7
·
0⤊
0⤋
OK!
3x(-2square2+3) =
I'm taking "2square2" to mean 2 squared or 2^2 = 4.
So, 3x (-4 +3)= -3x
2006-12-15 08:05:22
·
answer #2
·
answered by Jerry P 6
·
0⤊
0⤋
3x(-2^2)(2+3)
-2^2 multiplyed by 2 = -8
( -8 + 3 ) = -5
3x(-5) = -15x
Answer: -15x
2006-12-15 08:19:19
·
answer #3
·
answered by Wise Young Sage 2
·
0⤊
0⤋
3x(-2square2+3 = 3x(-2^2+3)
= 3x(4+3)=7*3x= 21x
ta-da!!!
2006-12-15 08:11:56
·
answer #4
·
answered by pooja_sarkar 2
·
0⤊
0⤋
3x * - 4 = -12x
3x * 3 = 9x
-12x + 9 x = -3x
2006-12-15 08:10:46
·
answer #5
·
answered by qwazer 2
·
0⤊
0⤋
3x(-2^2+3)
3x(4+3)
21x
2006-12-15 09:14:35
·
answer #6
·
answered by Anonymous
·
0⤊
0⤋
i comprehend i like: My contacts :D they're all horny, Princess of Y!A even nevertheless she does not love her puppy returned Molly she jogs my memory of a few thing stable haha Rick James- he's a hater nevertheless lmao Raul i will do you sometime quickly Mr. track- he jogs my memory of track and that i'm in love with track. Wtf singles and relationship? Haha next time I could look at the place the question is starrrred lmao.
2016-12-30 11:56:16
·
answer #7
·
answered by frahm 3
·
0⤊
0⤋
3x(-2x^2+3)=-6x^3+9x
2006-12-15 10:32:26
·
answer #8
·
answered by yupchagee 7
·
0⤊
0⤋
well...
3x(4.2+3)=33x
If i got it right....
2006-12-15 08:12:35
·
answer #9
·
answered by Mett 2
·
0⤊
0⤋